Execuções judicial e extrajudicial no Sistema Financeiro da Habitação: Lei No. 5.741/71 e Decreto-Lei No. 70/66 - Denardi, Volnei Luiz (2005)
The development of the topic judicial and extra-judicial executions in the Housing Financial Systems, governed by Law No. 5741/71 and by Law-Decree No. 70/66, respectively, has as main object to deal with the polemic issues involving these procedures, created under a regime of exception with the purpose of promoting the economic and social development. Although much quicker than the traditional legal procedures, reaching the so much desired scope by means of an alternative and quick way of solving conflicts, the extra-judicial execution still arises controversies in legal scholarship and case law, even over nearly 40 years after the enactment of Law-Decree No. 70/66. Notwithstanding the favorable standpoint taken by the Federal Supreme Court, the constitutional aspects of this procedure still are under discussion, thereby originating issues related to the due process of law, from which issues related to contestation, impartiality and natural judge are derived. No less effective, the procedure established by Law No. 5741/71, destined to the special mortgage execution of contracts entered into within the Housing Financial System, differentiating it from the common procedure of the Civil Procedural Code in face of the suppression of some execution acts, as well as of the limitation of the borrower s equity liability to the excussion of the property mortgaged in the loan contract collateralized by a mortgage. In the special mortgage execution, the debtor can submit the same defenses applicable to the common execution procedure against a solvent debtor contemplated by the Civil Procedural Code, such as debtor s embargoes, intraprocedural defense, and defenses carried out through autonomous information actions. We can highlight, as to the means of defense, the non-suspensivity of debtor s embargoes until the mortgaged property disoccupation.